The search for al Qaeda its leadership, ideology, and future - Riedel, Bruce O.; ProQuest (Firm) (Washington, D.C. : Brookings Institution Press, 2008)
"Profiles the most important figures in the al Qaeda movement---Osama bin Laden, Ayman Zawahiri, Abu Musaib al Zarqawi, and Mullah Omar, giving a comprehensive analysis of its origins, leadership, ideology, and strategy. Focuses more closely on what has happened to al Qaeda since 9/11 and outlines its ultimate goals"--Provided by publisher.
The Manhattan raid -- The thinker : Zawahiri -- The knight : Osama -- The host : Mullah Omar -- The stranger : Zarqawi -- Al Qaeda's plans -- How to defeat al Qaeda.
Includes bibliographical references (p.167-170) and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Zawahiri, Ayman; Bin Laden, Osama, -- 1957-2011.; Muhammad Omar, -- Mullah, -- 1960-; Zarqawi, Abu Musab, -- 1966-2006.; Qaida (Organization); Terrorism; Ideology; Leadership; Electronic books